Combination Learning Models with Technology to Hone Critical Minding Patterns on National Insights - Ramen Antonov Purba (Universitas Pendidikan Ganesha, 2022)
The challenges of the world of education are getting tougher. Students no longer think logically and lose their critical thinking patterns. Moreover, since the covid-19 pandemic situation causes learning must be switched to online learning. Most teachers use WhatsApp to conduct the learning process. But the impact of this learning is not maximum which makes students passive and learning is centered only on the lecturer. It is necessary to find a learning model that can improve students' critical thinking patterns. The research conducted will combine the cooperative learning type time token with the zoom application. The purpose of the research is whether there is a combined effect of the cooperative learning type time token with the zoom application on students' critical thinking in the citizenship course on national insight. Research approach with a quasi-experimental design. The control and experimental samples were a total of 62 students. The control group learns citizenship with WhatsApp, and the experimental group learns with a combined cooperative learning type time token with the zoom application. Data analysis with homogeneity test, normality test, and hypothesis testing. The results obtained are Sig value two tails at the number 0.00, which is smaller than the number 0.05. Ho is unacceptable, and Ha is acceptable. The critical mindset of students who use the time token type of cooperative learning model using the zoom application is better than students who learn to use WhatsApp.